Piezometry of the Aquifer of the Continental Terminal in the Borehole Fields of Godomey and Ouedo for the Delimitation of the Protection Areas around Boreholes of Ouedo - ZEVOUNOU, CRÉPIN; ALASSANE, ABDOU KARIM; KAKI, CHRISTOPHE; BACHAROU, TAOFIC; Koudemekpo, Joanèle (My University, 2017)
Groundwater is naturally protected against pollution through its filter layer which is the soil. However, the development of human activities, including the use of chemicals, gradually reduces the purifying action of this layer. It is therefore essential to develop strategies for a better management of this precious resource. The general objective of this work is to establish the piezometry of the aquifer of the Continental Terminal in the borehole fields of Godomey and Ouedo to improve the delineation of protection perimeters around the boreholes of Ouedo. The study was conducted using three methods that were the FCR method, the infiltration method and the method of Krijgsman and Lobo-Ferreira. The exploitation of the piezometric map enabled to obtain the hydraulic gradient of 0.165%. The radii of immediate protection’s perimeters (PPI) range from 55.653 m to 99.755 m. The retained close protection’ perimeters (PPR) and remote protection’s perimeters (PPE) have an ellipsoidal shape. Their upstream radii range from 220.72 m to 390 m for PPR and from 356.52 m to 659.52 m for PPE; the downstream radii range from 213.06 m to 387.25 m for PPR, and from 321.28 m to 603.97 m for PPE; the radii perpendicular to the flow direction to the right of each borehole vary from 212.58 m to 381.16 m for PPR, and from 336.11 m to 602.67 m for PPE. Probable risks identified for groundwater contamination in these protection areas are the discharge of domestic waste water, solid wastes and the use of chemical fertilizers and pesticides in farming practices.
Keywords: Groundwater; Anthropogenic Activities; Protection Perimeter; Piezometry